Pemanfaatan Daur Ulang Kertas Bekas Pada PT. Transportasi Jakarta Menjadi Nilai Tambah Bagi Kesejahteraan Masyarakat Binaan Bank Sampah Kumala - Ahmad Maulidizen; Abdul Chakim; Ayi Ganea; Dedeh Anggraini; Mugiyono Mugiyono; Muhammad Hasby Fauzi; Umar Limber; Yustriana Yustriana (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
This Community Empowerment Program aims to enhance the well-being of the community around PT. Transportation Jakarta through the utilization of recycled paper. The initiative focuses on collaboration with Bank Sampah Kumala to create added value from the paper recycling process. Firstly, education is provided to the community and employees of PT. Transportation Jakarta about the importance of paper recycling and its positive environmental impact. Subsequently, a partnership is established with Bank Sampah Kumala to collect used paper from PT. Transportation Jakarta. The used paper is then processed through an environmentally friendly recycling process. This community service provides dual benefits. First, it reduces the amount of paper waste entering landfills, potentially mitigating negative environmental impacts. Second, the recycled paper products are sold, providing additional income to the community under the care of Bank Sampah Kumala. The increased income is expected to contribute positively to the well-being of the surrounding community. By involving PT. Transportation Jakarta and Bank Sampah Kumala, this community service creates synergy between the company, the community, and waste management institutions. Thus, the project not only generates a positive impact on paper waste management but also enhances community well-being through additional income